Effect of Corn Row Spacing on Herbicide Effectiveness for Weed Control - Sarah H. Lancaster; Eric Adee; Igor G. R. Lima (Kansas Agricultural Experiment Station Research Reports, 2025)
Cultural weed control practices, such as narrow row spacing, can be an essential component of successful weed management. In 2022 and 2023, experiments were conducted in the Kansas River Valley to evaluate the interactions of herbicide programs and corn row spacings on weed control and grain yield. There were no differences in weed control at a site with low weed density in either year. However, at a site with a greater density of Palmer amaranth, Resicore + Acuron resulted in the greatest weed control, in either 15- or 30-inch row spacing. Degree + Callisto applied in 30-inch rows provided the best performance in both locations.
Keywords: row spacing; interactions; weed density